2016
DOI: 10.1186/s12872-016-0250-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor–15 predicts the prognoses of patients with acute coronary syndrome: a meta-analysis

Abstract: BackgroundRecent studies have shown Growth differentiation factor–15 (GDF-15) that is a member of the transforming growth factor β (TGF-β) superfamily might be a potential predictive cytokine for the prognosis of Acute coronary syndrome (ACS). However, there are discrepancies in these studies.MethodsPublication searches of the PubMed/Medline and EMBASE databases were performed without any time or ethnicity restrictions. The inclusion and exclusion criteria, when clear, were addressed. Random effects models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
0
30
0
3
Order By: Relevance
“…Two studies were conducted on meta‐analysis of the relationship between GDF‐15 and the different prognosis of acute coronary syndromes and heart failure separately. One of them, GDF‐15 is classified as a categorical variable for statistical analysis, and the other is as a continuous variable . In our meta‐analysis, 31 studies were included for the further integration analysis comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were conducted on meta‐analysis of the relationship between GDF‐15 and the different prognosis of acute coronary syndromes and heart failure separately. One of them, GDF‐15 is classified as a categorical variable for statistical analysis, and the other is as a continuous variable . In our meta‐analysis, 31 studies were included for the further integration analysis comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…The results from previous studies have shown that increased circulating GDF15 levels were closely associated with the development and progression of various cardiovascular diseases (including myocardial ischaemia/reperfusion, heart failure, atherosclerosis, and acute coronary syndrome), and were shown to be a strong and independent predictor of mortality and disease progression in patients with atherosclerosis and coronary artery disease [5][6][7][8][9][10][31][32][33][34][35][36]. In diabetic patients, higher levels of lipids and chronic inflammation may directly damage the cardiovascular system [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression and secretion of GDF15 can be strongly induced in the case of cardiovascular injury, such as pressure overload, myocardial infarction, heart failure, and atherosclerosis [4]. In recent years, a series of clinical studies [5][6][7][8][9][10] have reported that high circulating GDF15 levels are an independent predictive factor for several cardiovascular diseases in patients with atherosclerosis and acute coronary syndrome, and that investigating the levels of GDF15 could improve risk prediction beyond traditional risk factors and biochemical indicators.…”
mentioning
confidence: 99%
“…GDF-15 expression is dramatically upregulated in cardiovascular disease, and the incidence of cardiovascular events is positively correlated with the concentration of GDF-15 [153,154], suggesting its potential value as a disease biomarker. Meta-analysis shows that high levels of GDF-15 may increase the risk of mortality in patients with cardiovascular diseases [155,156]. GDF-15 is an independent predictor of all-cause mortality in ACS patients, adding incremental value to traditional risk factors and to NT-proBNP and C-reactive protein levels [157,158].…”
Section: 37mentioning
confidence: 99%